Prevalencia de Fasciola hepática en Ganado Bovino Faenado en el camal municipal Metropolitano de la Ciudad de Quito - Llanos Ugsha, Luis Alfredo (2024)
The causes of confiscation during the health inspection of slaughtered cattle represent a significant economic loss and a potential risk to public health, animal health, the environment, and biodiversity. Details such as the origin, sex, breed, and age of each slaughtered animal at the Metropolitan Municipal Slaughterhouse of Quito will be documented. Furthermore, the evaluation of the livers of these cattle will be conducted as part of a study aiming to gather information from 2400 specimens. A descriptive cross-sectional study was carried out, using proportion comparison tests and chi-square to analyze the association between variables, with the assistance of the statistical program InfoStat. A total of 2400 cattle samples were examined at the Metropolitan Municipal Slaughterhouse of Quito, finding 81 positive cases in July and 70 in August, totaling 151 cases of distomatosis. All slaughtered animals were included in the study. The identification of parasites was carried out macroscopically, focusing on the affected organs, mainly the liver and bile ducts, where the parasite typically develops the disease.